EMPOWERING YOUTH: SOCIAL TRANSFORMATION AND ISLAMIC LAW'S IMPACT ON CHILD RIGHTS - Karimullah, Suud Sarim (Ilmu Hukum, Sharia and Law Faculty, Sunan Gunung Djati Islamic State University of Bandung, 2023)
This study aims to understand the role of Islamic law in empowering youth and its impact on protecting children's rights in a social context by analyzing the challenges and opportunities that exist in defending children's rights within the framework of Islamic law. The literature study method is used by collecting information from relevant sources such as books, journals, and related documents. The results show that Islamic law provides a robust framework for each child to contribute to society through values such as Justice, balance, and social responsibility. Implementing children's rights in Islamic law creates holistic growth and positive social change. Educational institutions, families, communities, and the state are essential in upholding the child's rights. Despite challenges such as diverse interpretations, gender imbalances, and social problems, opportunities lie in the flexibility of Islamic law and the involvement of activists and civic organizations. By optimally utilizing the role of Islamic law, involving all parties, and overcoming existing challenges, there can be sustainable social transformation and fulfillment of children's rights within the framework of Islamic law.